Peasant autonomy : seed-saving practices of maize in rural Jalisco, Mexico - Lindqvist, Klara (SLU/Dept. of Urban and Rural Development, 2021)
The debate of maize seeds in Mexico has been, and is, intense and divided, with large seed companies on one side, mass-producing improved maize seeds and lobbying for the introduction of transgenic maize cultivation, and on the other side activists wanting to conserve and protect the native maize seeds. Farmers in Mexico have been facing large changes since the signing of the North American Free Trade Agreement. Competition from industrialized farms in the US and Canada has pressured Mexican farmers to raise yields and challenging the traditional agriculture and seed-saving practices. In the middle of all this there are Mexican peasants refusing to give up their traditional agriculture, holding on to their traditional seeds and seed saving systems. The purpose of this thesis is to investigate what motivates these peasants to continue saving traditional maize seeds, and hold on to organic farming, and how they relate to the situation of seeds and agriculture in Mexico. I investigated this through five months field work with a local seed-saving organisation in the region of Jalisco. I participated in their meetings with peasant farmers and performed in-depth interviews with selected peasants involved in the organizations’ work. I draw on the concepts of commodities and anti-commodities to show how peasants chose to keep traditional maize seed and practices as a form of resistance to the commodity agriculture that has come to dominate in Jalisco. My findings also show that the values of saving one’s own maize seeds are going beyond purely economic ones, and include values of history and traditions, values connected to taste and texture and values of the human-nature relationships. In particular, autonomy is found to be a central value in the process of obtaining seeds, and an explanation to why farmers expresses such a strong opposition to buying improved seed.